Effect of Holding Temperature to Bainite Transformation in Cr Mo Steel - M., Sarizam; H., Terasaki; Y., Komizo (2013)
The effect of holding temperature to variant selection mechanism during bainite transformation was investigated in 2Cr-1Mo steel. The behavior of transformation has been studied by using high temperature laser scanning confocal microscopy, LSCM via in situ observation. The specimen was heat treated to 1350℃ and hold for 60s before being cooled to 560℃and 580℃. At both conditions, each specimen was isothermally transformed for 1 hour and cooled to room temperature. The heat treated specimen was then analyzed by using electron backscattered diffraction, EBSD method. As a result, variant preferential selection is more prominent in higher holding temperature which coarsened the block and packet boundary is connected with low misorientation angle variant.